2017
DOI: 10.1186/s12876-017-0570-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of post-ERC infectious complications in patients with biliary obstruction by adding antimicrobial agents into ERC contrast media- a single center retrospective study

Abstract: BackgroundPatients with biliary obstruction are at high risk to develop septic complications after endoscopic retrograde cholangiography (ERC). We evaluated the benefits of local application of antimicrobial agents into ERC contrast media in preventing post-ERC infectious complications in a high-risk study population.MethodsPatients undergoing ERC at our tertiary referral center were retrospectively included. Addition of vancomycin, gentamicin and fluconazol into ERC contrast media was evaluated in a case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Recent studies are summarized below: ▪ A nationwide prospective study (31 188 patients) found, after adjustment for confounders, a 26 % risk reduction in postoperative adverse events when prophylactic antibiotics were used (OR 0.74, 95%CI 0.69 -0.79) [119]; nevertheless, the absolute risk reduction in adverse events (2.6 % in unselected patients and 3.8 % in patients with obstructive jaundice) was estimated to be insufficient by the authors to justify routine antibiotic prophylaxis in unselected patients; ▪ A prospective study (183 unselected patients) found similar incidences of cholangitis with vs. without antibiotic prophylaxis, and all patients who developed cholangitis had incomplete drainage [120]; ▪ A retrospective series (605 unselected patients) found that the increase in the incidence of post-ERCP cholangitis after routine antibiotic prophylaxis had been abandoned (1.7 % vs. 2.0 %) was not statistically significant [121]. In that study, sclerosing cholangitis and incomplete biliary drainage were significant risk factors for postoperative cholangitis; ▪ Another retrospective study (84 procedures, mostly in patients with sclerosing cholangitis) suggested that addition of antibiotics and antifungal agents to the contrast medium was associated with a lower risk of post-ERCP infectious complications (OR 0.33, 95%CI 0.11 -0.98), in particular in patients with incomplete biliary drainage [122].…”
Section: Recommendationmentioning
confidence: 96%
“…Recent studies are summarized below: ▪ A nationwide prospective study (31 188 patients) found, after adjustment for confounders, a 26 % risk reduction in postoperative adverse events when prophylactic antibiotics were used (OR 0.74, 95%CI 0.69 -0.79) [119]; nevertheless, the absolute risk reduction in adverse events (2.6 % in unselected patients and 3.8 % in patients with obstructive jaundice) was estimated to be insufficient by the authors to justify routine antibiotic prophylaxis in unselected patients; ▪ A prospective study (183 unselected patients) found similar incidences of cholangitis with vs. without antibiotic prophylaxis, and all patients who developed cholangitis had incomplete drainage [120]; ▪ A retrospective series (605 unselected patients) found that the increase in the incidence of post-ERCP cholangitis after routine antibiotic prophylaxis had been abandoned (1.7 % vs. 2.0 %) was not statistically significant [121]. In that study, sclerosing cholangitis and incomplete biliary drainage were significant risk factors for postoperative cholangitis; ▪ Another retrospective study (84 procedures, mostly in patients with sclerosing cholangitis) suggested that addition of antibiotics and antifungal agents to the contrast medium was associated with a lower risk of post-ERCP infectious complications (OR 0.33, 95%CI 0.11 -0.98), in particular in patients with incomplete biliary drainage [122].…”
Section: Recommendationmentioning
confidence: 96%
“…Noticeably, cholangitis was less frequently observed in the SBS group than in the SIS group. Several studies have demonstrated that incomplete biliary drainage is a significant risk factor for postoperative cholangitis [19][20][21]. In patients with Bismuth III and IV strictures, more than two stents are often required to drain all opacified ducts [16].…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, cholangitis was less frequently observed in the SBS group than in the SIS group. Several studies have demonstrated that incomplete biliary drainage is a signi cant risk factor for postoperative cholangitis (19)(20)(21). In patients with Bismuth III and IV strictures, more than two stents are often required to drain all opaci ed ducts (16).…”
Section: Discussionmentioning
confidence: 99%